Nurse and Midwife Clinical Competency Determination and Competency Development Planning Toolkit. - HIGGINS, AGNES; TIMMINS, FIONA; BEGLEY, CECILY; NEVIN, MARY (National Council for the Professional Development of Nursing and Midwifery, 2010)
The Irish health service is driven by policy direction aiming to provide more services within primary, community and continuing care. A programmatic approach to change is being taken by the Health Service Executive with an initial focus on chronic disease. The current healthcare environment within which nurses and midwives now work has intensified working processes and increased patient complexity. Patient populations are ageing, those with chronic diseases are living longer, hospital stays are shorter with increased use of technology and invasive treatments, patients present with co-morbidities and multiple pathologies, patient turnover and subsequent admissions and discharges are increased and care in the community is expanding. Patient safety and risk controls necessitate on-going clinical audit, utilization of evidence-based practice, adherence to clinical guidelines, introduction of care pathways and peer review. This means that processes for determining and attainment of competencies for nurses and midwives building on identified core clinical competencies are required with due regard to scope of practice and service need. Modern developments such as service needs analysis, the maintenance of portfolios, engagement in clinical supervision and clinical audit and other continuing professional development processes provide support for clinical competency determination and attainment. To this end the National Council commissioned the School of Nursing and Midwifery, Trinity College Dublin, through an open tender process to develop and test a toolkit to assist service managers, nurse and midwife managers and nurses and midwives in clinical competency determination and competency development planning. The research team worked in partnership with a clinical team and a National Council steering committee to develop the toolkit. This report details the process involved in developing the toolkit. The development of the toolkit was informed by a literature review, examination of grey literature and piloting of a toolkit. It built upon current competency frameworks for nurses’ and midwives’ and documents published by the National Council. The final piloted toolkit includes information on: competence determination for service need, identifying and writing clinical competencies for practice; competency development planning and assessment and competency frameworks in Nursing and Midwifery. The toolkit was evaluated using a mixed-method approach in sixteen pilot sites. A purposive sample of 455 registered nurses or midwives, to ensure representation of discipline, profession, grade and area of practice, were recruited to participate in the survey aspect of the pilot. In total 208 questionnaires were returned representing 46% of the total number distributed. The questionnaires sought experiences of using competencies, and opinions on the structure, content, relevance and utility of the toolkit, plus feedback on using the tools provided within the toolkit. Participants were also given the opportunity to provide opinions on how to improve the toolkit in an open response section, a demographic section was also included. In total, 45 people (73% response rate) also participated in six focus group interviews. A semi-structured interview schedule developed by the team was used to guide the discussion.
PUBLISHED
Dublin
Keywords: Irish Health Service; Inclusive Society